Impairment in insulin secretion without changes in insulin resistance explains hyperglycemia in patients with acromegaly treated with pasireotide LAR. Issue 12 (17th November 2022) - Wolf, Peter; Dormoy, Alexandre; Maione, Luigi; Salenave, Sylvie; Young, Jacques; Kamenický, Peter; Chanson, Philippe
Abstract : Objective: Pasireotide is a second-generation somatostatin receptor ligand (SRL) used for treating acromegaly. Its clinical use is limited by adverse effects on glucose homeostasis. The aim of this study was to evaluate longitudinal changes in beta-cell function and insulin sensitivity associated with pasireotide in patients not controlled by first-generation SRLs. Design: We performed a retrospective study. Methods: The efficacy (growth hormone (GH)/insulin-like growth factor (IGF-1) concentrations; tumor size) and effect on glucose homeostasis were analyzed in 33 patients. Longitudinal data on oral glucose tolerance tests were available before, shortly (mean ± s.d., 6.1 ± 3.8 months) and long term (24.4 ± 11.1 months) after initiation of pasireotide in 14 patients. Insulin secretion (insulinogenic index; disposition index) and insulin sensitivity were calculated by validated indices. Results: Pasireotide-induced diabetes occurred in 12 patients (36%). It was mediated by impaired insulin secretion, which occurred shortly after initiation of treatment and then remained stable on long term (insulinogenic index, median (min; max), 80 (12; 542) vs 16 (6.4; 101) vs 25 (3.7; 396) pmol/mmol, respectively; P = 0.028; disposition index, 1.45 (0.42; 4.88) vs 0.53 (0.17; 2.63) vs 0.60 (0.22; 1.71), respectively; P = 0.024). No significant changes in insulin sensitivity were observed, despite a marked reduction of GH/IGF-1 concentrations. Older age and a worse glycemic control at baseline were the strongest predictors for hyperglycemia and the need for antidiabetic treatment. Conclusion: Worsening of glycemic control during pasireotide therapy is caused by an impaired insulin secretion, whereas insulin sensitivity is not affected. These findings might be important for the choice of antidiabetic treatment for pasireotide-induced hyperglycemia. Significance statement: Pasireotide, a second-generation SRL used for treating acromegaly, may be associated with glucose metabolism impairment. In a retrospective study of 33 patients, we observed that treatment with pasireotide was associated with normalization of serum IGF-1 in almost 60% of patients, but one-third of patients developed diabetes. In the patients who stopped pasireotide because of hyperglycemia, HbA1c promptly decreased. Longitudinal data in 14 patients show that diabetes is mediated by impaired insulin secretion, which occurred shortly and then remained stable on long term, while no significant changes in insulin sensitivity were observed, despite a marked reduction of GH/IGF-1 concentrations. Older age and a worse glycemic control at baseline were the strongest predictors for hyperglycemia.